2008
DOI: 10.1016/j.bandl.2007.09.002
|View full text |Cite
|
Sign up to set email alerts
|

When nominal features are marked on verbs: A transcranial magnetic stimulation study

Abstract: It has been claimed that verb processing (as opposed to noun processing) is subserved by specific neural circuits in the left prefrontal cortex. In this study, we took advantage of the unusual grammatical characteristics of clitic pronouns in Italian (e.g., lo and la in portalo and portala 'bring it [masculine]/[feminine]', respectively)-the fact that clitics have both nominal and verbal characteristics, to explore the neural correlates of verb and clitic processing. We used repetitive transcranial magnetic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 43 publications
(2 reference statements)
1
8
0
Order By: Relevance
“…This observation leads to the expectation thatwhile uninflected noun or verb stems mayreadilyaccess lexicalrepresentations, the presenceofanaffix in inflected verbs mayplace additional demands on this access process. Activation is observed onlyi nc ases in which there are structurali mplications to grammatical category knowledge.Asimilar conclusion is also reached by Finocchiaro et al (2008). These findingsare in line with later studies on morphological processing showing that the left middle temporal gyrus (LMTG)appears to be coactivated with the left inferior frontal gyrus (LITG) when morphologicallyc omplex words are processed.…”
Section: Distinction Between Nouns and Verbssupporting
confidence: 87%
See 2 more Smart Citations
“…This observation leads to the expectation thatwhile uninflected noun or verb stems mayreadilyaccess lexicalrepresentations, the presenceofanaffix in inflected verbs mayplace additional demands on this access process. Activation is observed onlyi nc ases in which there are structurali mplications to grammatical category knowledge.Asimilar conclusion is also reached by Finocchiaro et al (2008). These findingsare in line with later studies on morphological processing showing that the left middle temporal gyrus (LMTG)appears to be coactivated with the left inferior frontal gyrus (LITG) when morphologicallyc omplex words are processed.…”
Section: Distinction Between Nouns and Verbssupporting
confidence: 87%
“…In theirTranscranial Magnetic Stimulation (TMS) study, Finocchiaro et al (2008) focus on the neural correlates of verb and clitic processing.They used pronominal clitic pronouns in Italian (e. g., portala 'bring it[feminine]')w hich have both nominal and verbal characteristics.T hey have nominal characteristics since clitics have nominal referents and are specified for nominal features (e. g.,g ender). They have verbal properties since they attach to verbs and depend syntacticallyand phonologicallyontheir verbalhosts.…”
Section: Tms Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Note, however, that the verb-specific activation found here is not modulated by the semantic category (action vs. non-action) of the stimuli, despite the fact that the action/non-action contrast has been proven to give rise to different activation patterns (Kaplan & Iacoboni, 2007;Khader, Jost, Mertens, Bien, & Rosler, 2010;Noppeney, Josephs, Kiebel, Friston, & Price, 2005;Oliveri et al, 2004). Second and more importantly, the verb-specific activation found here is within the region that recent rTMS studies have proven to be crucial for verb grammatical processing (Cappelletti et al, 2008;Finocchiaro et al, 2008;Shapiro et al, 2001). Of course, one could argue against the grammatical account also for those rTMS studies.…”
Section: Discussionmentioning
confidence: 54%
“…Supporting evidence has come from transcranial magnetic stimulation (TMS) that has shown that the ability to perform grammatical operations on verbs may be selectively disrupted following repetitive TMS (rTMS) of a well-defined portion of the left prefrontal cortex, just anterior and superior to Broca's area and clearly distinct from motor planning areas (Cappelletti, Fregni, Shapiro, Pascual-Leone, & Caramazza, 2008;Shapiro, Pascual, Mottaghy, Gangitano, & Caramazza, 2001). This finding reveals the importance of this area for verb morphosyntax (for further evidence, see Finocchiaro et al, 2008).…”
Section: Introductionmentioning
confidence: 86%